Determinar medidas de control de las enfermedades biomecánicas del personal operativo de la empresa Veolia Aguas de Tunja E.S.P S.A (2021)
“Ergonomics is a scientific discipline or human factors engineering, of a multidisciplinary nature, focused on the person-machine system, whose objective is the adaptation of the work environment or conditions to the person in order to achieve the best possible harmony between optimal comfort conditions and productive efficiency” (Rada, 2013).